Pelatihan Soft Skill “Mengakses, Menganalisis dan Mensintesis Informasi (AAS)” untuk Meningkatkan Literasi Informasi Digital dan Kemampuan Analisis Akuntansi Mahasiswa STIE Tri Bhakti - Reni Suwandi Ade Puspita (Lembaga Pengembangan Kinerja Dosen, 2026)
The digital era has created information overload, making it easier for students to access information but more difficult to identify credible sources. This condition increases the risk of misinformation and weak critical thinking, especially among Generation Z students who heavily rely on social media platforms. This community service program aimed to improve students’ soft skills in accessing, analyzing, and synthesizing information (AAS), particularly to support accounting and management decision-making. The training was conducted on October 1, 2025, at STIE Tri Bhakti, involving accounting and management students. The implementation methods included lectures, interactive discussions, demonstrations, case studies, and simulation-based practices. The materials emphasized identifying credible sources (OJK, IDX, BPS, annual reports, and academic journals), evaluating information validity using the 5W1H approach, analyzing financial statement cases, and synthesizing data into executive summaries and recommendations. The results indicate that participants showed improved awareness of source credibility, increased critical thinking skills in interpreting accounting information, and better ability to formulate structured conclusions. This program contributes to strengthening students’ analytical mindset and preparing them for academic tasks and professional accounting practices in the digital era.